Self-assembly of nanostructured PbS for solar photovoltaic applications - Hawaldar, Ranjit R.; Kanade, K. G.; Patil, K. R.; Sathaye, S. D.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Materials Chemistry and Physics, 2005)
In the present communication, the self-assembly of nanocrystalline PbS at the liquid-liquid interface is reported. The PbS nanocrystals were, subsequently, transformed in the form of thin films by dip coating. The resultant Q-PbS films were characterized by SEM-EDAX, TEM-SAED, XRD, XPS and UV-vis Spectroscopy. Pyramidal features at the nanometer scale, preferred orientation along (2 2 0) and (4 0 0) planes of cubic structure and a sharp excitonic peak at 656 run are the salient aspects of this work. The band-gap of the order of 1.8 eV (associated with the excitonic feature) is ideally suited for solar photovoltaic applications. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid interface; nanopyramid; Nanostructures; PbS

Studies on gas sensing performance of pure and modified barium strontium titanate thick film resistors - Jain, G. H.; Patil, L. A.; Patil, P. P.; Mulik, Uttam P.; Patil, K. R. (Bulletin of Materials Science, 2007)
Barium strontium titanate ((Ba0.87Sr0.13)TiO3-BST) ceramic powder was prepared by mechanochemical process. The thick films of different thicknesses of BST were prepared by screen-printing technique and gas-sensing performance of these films was tested for various gases. The films showed highest response and selectivity to ammonia gas. The effect of film thickness on gas response was also studied. As prepared BST thick films were surface modified by dipping them into an aqueous solution of titanium chloride (TiCl3) for different intervals of time. Surface modification shifted response to H2S gas suppressing the responses to ammonia and other gases. The surface modification, using dipping process, altered the adsorbate-adsorbent interactions, which gave the unusual sensitivity and selectivity effect. Sensitivity, selectivity, thermal stability, response and recovery time of the sensor were measured and presented.
Keywords: (Ba0.87Sr0.13)TiO3 thick films; ammonia gas sensor; II2S gas sensor; selectivity; sensitivity